If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3x + -2) + 9x = 0 Reorder the terms: 6(-2 + 3x) + 9x = 0 (-2 * 6 + 3x * 6) + 9x = 0 (-12 + 18x) + 9x = 0 Combine like terms: 18x + 9x = 27x -12 + 27x = 0 Solving -12 + 27x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 27x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 27x = 0 + 12 27x = 0 + 12 Combine like terms: 0 + 12 = 12 27x = 12 Divide each side by '27'. x = 0.4444444444 Simplifying x = 0.4444444444
| 3v^2+v+2=0 | | 3t-24+2t=7-1t | | -28-(-8)=x/9 | | 21+-14x=29+x | | (4+w)(5w-9)=0 | | 4p+2p-3x=x | | -9n+10= | | 3c-24=96 | | 3y-8+5(-5)=3(-5)+10 | | -7-3(-6n+8)=-121 | | y+y+5x-4y+7= | | 7(1-4x)=119 | | e^3x=6xe^3 | | 3y-8+5x=3x+10 | | 90=8/5x | | 7(3+4x)-8x=-99 | | 2.5x-1.7*(5-2x)=3x | | -7(-8x+6)+1=295 | | 5x+2y+3p+4y-p= | | 10=ay+3d | | 3t-24+2t=7-t | | 2+5x-1+5x= | | 5t-8=28 | | 14+1=-3(3x-5) | | 10x-3y+3x-4y= | | graphm(x)=5x | | 1.7x+9.1x=-32.4 | | p(x)=.33x | | 10x-3y+3p+4y-p= | | 1.2x=-2.4 | | X+7+X-3=200 | | 5x-2y+2x+6y= |